PERAN DANA SOSIAL (WAQF) DALAM MENDORONG PERTUMBUHAN EKONOMI DAN PENGENTASAN KEMISKINAN DI NEGARA-NEGARA MUSLIM - Camelia; Minhatus Sania; Dava Dhito Sasiaji; Muhammad Taufiq Abadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The welfare of Islamic countries is always in the spotlight. It is recorded that around 27.2 percent of the total population of Islamic countries has an income of around 15 thousand rupiah. This illustrates that Islamic countries experience economic difficulties compared to other countries in the world. One of the instruments in efforts to encourage economic growth and efforts to eradicate poverty in Muslim countries in particular is through social funds (waqf). Waqf is one of the instruments in improving economic welfare and alleviating poverty. The research we conducted aims to examine the extent of the role of waqf in realizing the economic welfare of society and the country's economy. The method used in this research is a qualitative method with a literature study approach by taking relevant sources as references for the research we conducted. The research we conducted showed that social funds (waqaf) have a very big role in efforts to alleviate poverty in Islamic countries. One way is the cash waqf approach, although it has not been used optimally, cash waqf has a role in reducing poverty. The government's role is also very important in controlling waqf social funding institutions.